MANAJEMEN PRODUKSI PROGRAM SIARAN BERITA LOKAL GATRA BALI DI LPP TVRI BALI - Aan Darmawan, I Gusti Ngurah (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2025)
This study analyzes the production management of the "Gatra Bali" broadcast program on LPP TVRI Bali in the context of digital television broadcasting. This program is a Balinese-language news show featuring two main segments: current news and cultural and Hindu religious-themed feature stories. The study employs a qualitative descriptive approach using direct observation of the production process both inside and outside the studio, along with in-depth interviews with production team members. The results indicate that the production stages include pre-production (concept planning, research, scriptwriting), production (filming and interviews), and post-production (editing and content finalization). The challenges faced during production involve limited human resources, minimal production budget, and insufficient audience feedback. Strategies implemented to maintain program quality include optimizing existing resources, enhancing the production team's capacity, and strengthening creative concepts in each broadcast. This study applies Systems Theory, which examines the production process through the elements of input, process, output, and feedback. These findings provide significant insights into understanding the dynamics of local television production focused on cultural preservation in the digital broadcasting era